Child maltreatment and resilience in adulthood: A systematic review and meta-analysis - Fares-Otero, Natalia E. (2025)
We conducted a systematic review and meta-analysis to quantify associations between overall and subtypes of CM, global/trait resilience, and five resilience domains (coping, self-esteem, emotion regulation, self-efficacy, and well-being) in adults, and to examine moderators and mediators of these associations. A systematic search was undertaken on 12 June 2024 to identify published peer-reviewed articles in five databases (PROSPERO-CRD42023394120). Of 15,262 records, 203 studies were included, comprising 145,317 adults (M age = 29.62 years; 34.96% males); 183 studies and 557 effect sizes were pooled in random-effect meta-analyses. Overall CM and its subtypes were negatively associated with global/trait resilience and its domains (r = -0.081 to -0.330). Emotional abuse/neglect showed the largest magnitude of effect (r = -0.213 to -0.321). There was no meta-analytic evidence for an association between sexual abuse and coping, and physical abuse/neglect and self-esteem. Meta-regressions identified age, sample size, and study quality as moderators. Subgroup analyses found that associations between emotional abuse and emotion regulation were stronger, while associations between emotional abuse and self-esteem were weaker, in western versus non-western countries. No differences were found in associations between CM and resilience in clinical versus non-clinical samples. Narrative synthesis identified several mediators. Associations were of small magnitude and there were a limited number of studies, especially studies assessing CM subtypes, such as physical neglect, bullying, or domestic violence, and resilience domains, such as coping or self-efficacy, in males, and clinical samples. CM exposure negatively impacts resilience in adults, an effect observed across multiple maltreatment types and resilience domains. Interventions focused on resilience in adults with CM histories are needed to improve health and psychosocial outcomes.